How Can We Increase Pro-environmental Behavior During COVID-19 Pandemic? Focusing on the Altruistic (vs. Egoistic) Concerns - Kim, Yaeri; Lee, Seojin Stacey (Frontiers in Psychology, 2022)
Would the life-threatening pandemic impact pro-environmental behavior? This study demonstrates the effects of coronavirus disease 2019 (COVID-19) on pro-environmental product consumption. Two experimental studies manipulated individuals’ COVID-19 concerns and the presence/absence of pro-environmental prompts. In study 1, we found that consumers indicated lower purchase intention for a product with the environmental prompts when recalling COVID-19 concerns compared to normal situations. In study 2, we disentangled egoistic COVID-19 concerns (e.g., concerns about disadvantages to individuals’ work and finances) from altruistic COVID-19 concerns (e.g., concerns about damage to the country’s economy) and investigated the effects of both these concerns on pro-environmental product consumption. The results of study 2 revealed that consumers reported an increased purchase intention toward the e-prompt products, which manipulated altruistic COVID-19 concerns. However, the presence/absence of e-prompt products did not affect consumers’ purchase intentions when recalling egoistic COVID-19 concerns. Concerns regarding environmental, social, and corporate governance (ESG) issues mediated the interaction effect between the type of COVID-19 concerns and the presence/absence of e-prompts for the products.